2022
DOI: 10.3390/antiox11091790
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Implication in Retinal Diseases—A Review

Abstract: Oxidative stress (OS) refers to an imbalance between free radicals (FRs), namely highly reactive molecules normally generated in our body by several pathways, and intrinsic antioxidant capacity. When FR levels overwhelm intrinsic antioxidant defenses, OS occurs, inducing a series of downstream chemical reactions. Both reactive oxygen species (ROS) and reactive nitrogen species (RNS) are produced by numerous chemical reactions that take place in tissues and organs and are then eliminated by antioxidant molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Over the past 40 years, various of medical fields, including ophthalmology, have extensively studied the concept of ‘oxidative stress’ [ 26 ]. Oxidative stress specifically refers to an imbalance between free radicals, which are highly reactive molecules produced in our bodies through a variety of pathways, and intrinsic antioxidant capacity [ 27 ]. Oxidative stress is extremely complicated, connected to other types of stress, and has impacts on different cell types [ 28 ].…”
Section: Oxidative Stress and Rosmentioning
confidence: 99%
“…Over the past 40 years, various of medical fields, including ophthalmology, have extensively studied the concept of ‘oxidative stress’ [ 26 ]. Oxidative stress specifically refers to an imbalance between free radicals, which are highly reactive molecules produced in our bodies through a variety of pathways, and intrinsic antioxidant capacity [ 27 ]. Oxidative stress is extremely complicated, connected to other types of stress, and has impacts on different cell types [ 28 ].…”
Section: Oxidative Stress and Rosmentioning
confidence: 99%
“…In response, reactive oxygen species (ROS) and reactive nitrogen species (RNS) are generated at the retinal level. Many studies have revealed that ROS and RNS are important mediators of inflammation and ischemia, emphasizing the role of oxidative stress in promoting retinal vasculitis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress (OS) is the discrepancy among free radicals, i.e., reactive oxygen, nitrogen species, and advanced glycated-end products (AGEs), which are generally produced by several pathways and the intrinsic antioxidant scavenging system. Once free radicals rise, they overwhelm intrinsic antioxidant defenses (Nebbioso et al, 2022 ). Oxidative stress can damage lipids, carbohydrates, proteins, enzymes, and nuclear and mitochondrial DNA, as a consequence of which cell death is induced.…”
Section: Introductionmentioning
confidence: 99%